2020
DOI: 10.3390/jcm9082639
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Virtual Reality Rehabilitation in Patients with Knee and Hip Osteoarthritis

Abstract: Osteoarthritis (OA) is a common health problem leading to pain, limitation in physical function, a decrease in the quality of life and disability. OA affects 60–70% of the population above 65 years of age all over the world, and is associated with a high cost of healthcare. The main method of treatment of OA, apart from pharmacotherapy and surgery, is comprehensive rehabilitation. Advances in medical technology have resulted in the possibility of using computer-assisted interventions in rehabilitation. The pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
38
1
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 78 publications
(215 reference statements)
4
38
1
5
Order By: Relevance
“…[ 5 ] Post-operative progressive exercise program achieves faster recovery, better function, and improved range of motion (ROM). [ 6 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 5 ] Post-operative progressive exercise program achieves faster recovery, better function, and improved range of motion (ROM). [ 6 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 11 , 13 , 14 ] In orthopedic rehabilitation, the advantage of VR-based rehabilitation has been explored in patients with osteoarthritis, low back pain, and anterior cruciate ligament injury. [ 6 , 15 , 16 ] Although some studies have investigated the effect of VR equipment on TKA patients, [ 17 , 18 ] there is insufficient evidence to demonstrate the advantage of VR. A systematic review reported that VR-based rehabilitation has no benefit in increasing function, relieving pain, or increasing satisfaction following TKA compared to conventional rehabilitation.…”
Section: Introductionmentioning
confidence: 99%
“…In a review study conducted on the effectiveness of the telerehabilitation method (ie, virtual reality [VR]) in patients with knee OA, the effectiveness of VR-based rehabilitation was unclear; however, interventions based on VR were promising in managing pain and postural and proprioception training (40). In addition, VR-based rehabilitation is an expensive method, leading to financial problems for the users.…”
Section: Discussionmentioning
confidence: 99%
“…Conforme referido no início deste artigo existe ainda uma escassez da utilização de jogos no ensino à pessoa submetida a artroplastia da anca, o que não nos permite comparar os resultados nesta discussão (11,12) . Observam-se porém alguns dados mas referente à recurso à Nintendo e WI para a reabilitação (22)(23)(24) .…”
Section: Discussionunclassified
“…Os avanços recentes na tecnologia a resultaram numa introdução gradual de intervenções assistidas por computador na reabilitação. Nas últimas décadas, novas tecnologias em reabilitação foram desenvolvidas numa gama de tecnologias empregadas que variam de plataformas de jogos populares e baratos a sistemas altamente especializados com plataformas de hardware e software dedicadas (12) .…”
Section: Introductionunclassified